2021
DOI: 10.1177/2372732220983840
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Implicit Bias Training: Policy Insights for Increasing Organizational Diversity

Abstract: Many organizations are working to address diversity, equity, and inclusion. Organizations frequently use implicit bias to explain disparities and marshal implicit bias training as a solution. Implicit bias is difficult to change and trainings do not yield more diversity in organizations, so organizations should move beyond implicit bias trainings in their diversity, equity, and inclusion efforts. Organizations should (a) use trainings to educate members of their organizations about bias and about organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 87 publications
1
105
0
Order By: Relevance
“…While identity safety cues can be implemented by well-intentioned individuals and organizations who wish to appear inclusive or raise awareness (e.g., signaling support as allies; Chapman & Coffé, 2016), they can sometimes be used superficially by individuals and organizations in pursuit of their own goals (e.g., partaking in racial capitalism, rainbow capitalism, or performative gestures; Falco & Gandhi, 2020;Henry, 2016;Leong, 2013). As found in other research, intentions for building inclusion and diversity do not always equate impact (Kaiser et al, 2013;Kalev et al, 2006;Legault et al, 2011;Onyeador et al, 2021); It is therefore important to be mindful and critical of cue use and motivations. Racial capitalism and rainbow capitalism, for example, are processes by which identity safety cues could be harnessed for social and economic value owned by nonstigmatized entities (Falco & Gandhi, 2020;Leong, 2013).…”
Section: Ethical Considerationsmentioning
confidence: 90%
See 2 more Smart Citations
“…While identity safety cues can be implemented by well-intentioned individuals and organizations who wish to appear inclusive or raise awareness (e.g., signaling support as allies; Chapman & Coffé, 2016), they can sometimes be used superficially by individuals and organizations in pursuit of their own goals (e.g., partaking in racial capitalism, rainbow capitalism, or performative gestures; Falco & Gandhi, 2020;Henry, 2016;Leong, 2013). As found in other research, intentions for building inclusion and diversity do not always equate impact (Kaiser et al, 2013;Kalev et al, 2006;Legault et al, 2011;Onyeador et al, 2021); It is therefore important to be mindful and critical of cue use and motivations. Racial capitalism and rainbow capitalism, for example, are processes by which identity safety cues could be harnessed for social and economic value owned by nonstigmatized entities (Falco & Gandhi, 2020;Leong, 2013).…”
Section: Ethical Considerationsmentioning
confidence: 90%
“…promoting social inclusion and diversity (Cahan, 2020;Chamberlain, 2019;Washington & Newport, 2017). To that end, multiple broad approaches exist (see Kalev et al, 2006;Onyeador et al, 2021;Steele, 2010) to lessen biases among members of dominant groups (e.g., those advantaged by race, gender, or sexual orientation) and to increase inclusion among members of stigmatized groups (e.g., those disadvantaged by their social identities). Extensive reviews already detail "what works" and does not work in terms of bias and diversity trainings (e.g., Bezrukova et al, 2016;Carter et al, 2020;Chang et al, 2019;Onyeador et al, 2021), prejudice reduction strategies (e.g., Lai et al, 2014;Legault et al, 2011;Paluck et al, 2021), and other diversity-related initiatives (e.g., Brannon et al, 2018;Kaiser et al, 2013;Kalev et al, 2006).…”
Section: Public Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent popular example is implicit bias-based interventions to address issues of bias, racism, and inequities in organizations. Such interventions have become widespread, but evidence for their effectiveness for improving prejudice and inequity outcomes is sparse (FitzGerald et al, 2019;Onyeador et al, 2021). In a systematic review of implicit bias interventions, Forscher et al (2019) found that the large majority of studies were conducted with U.S. university students, focused only on changes in implicit attitudes versus broader outcomes, and reported small effects.…”
Section: Organizational Interventions: the Case Of Implicit Bias Trainingmentioning
confidence: 99%
“…Not only may these interventions be ineffective, but they appear to crowd out other actions that may better address systemic inequities (Pritlove et al, 2019). Organizational equity, diversity, and inclusion efforts should adapt to emphasize practices with stronger, more generalizable evidence bases such as intergroup contact and systems to bypass individual prejudice (Onyeador et al, 2021).…”
Section: Organizational Interventions: the Case Of Implicit Bias Trainingmentioning
confidence: 99%